Participatory, explorative, qualitative modeling: Application of the iMODELER software to assess trade-offs among the SDGs - Kai Neumann; Carl Anderson; Manfred Denich (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
The UN's Sustainable Development Goals (SDGs) in their generalized form need to be further reflected in order to identify synergies and trade-offs between their targets, and to apply them to concrete nations and regions. Explorative qualitative cause and effect modeling could serve as an approach for considering crucial factors to better understand the interrelations among the SDGs, eventually leading to more informed concrete measures that are able to cope with the SDG's inherent obstacles. This work describes a model that could serve as a template for concrete application. The generalized model already points to some potential trade-offs. Its first analysis cautiously raises doubts that some possible assumptions behind the SDGs might overlook systemic boundaries. For example, an undifferentiated increase of productivity contradicts a lessened environmental impact and need for resources in light of potential planetary boundaries. However, the model was developed as a starting point and requires modification for its application to a concrete region.
Keywords: A19; C19; B49; C38; C69; O10; O19; 330; SDG; transition; sustainability; modeling; explorative; participatory; qualitative; insight matrix; soft factors; feedback loops